CO2 reduction by photocatalytic and photoelectrocatalytic approaches over Eu(III)-ZnGa2O4 nanoparticles and Eu(III)-ZnGa2O4/ZnO nanorods. (June 2022) - Jang, Hye Ji; Yang, Ju Hyun; Maeng, Ju Young; Joo, Min Hee; Kim, Young Jun; Hong, Sung-Min; Rhee, Choong Kyun; Sohn, Youngku
Abstract: Value-added products by CO2 reduction have extensively been researched using many developed catalysts. Herein, Eu(III)-doped ZnGa2 O4 (ZGO) nanoparticles and ZGO hybridized ZnO nanorods (ZGO/ZnONR ) were evaluated for photocatalytic and photoelectrocatalytic CO2 reduction under diverse experimental conditions. For photocatalytic CO2 reduction, the CO/CH3 OH production ratio was > 1 for ZGO, but < 1 for ZGO/ZnONR . For electrochemical CO2 reduction, CO and H2 were major products with minor formate, and dependent on the parameters including Eu(III)-doping. H2 and formate were increased with increasing applied potential, and CO showed the highest Faradaic efficiency at −1.6 V (vs. Ag/AgCl). Syngas (H2 /CO) ratio was shown to be efficiently controlled from 0.5 to 2.0. UV light showed a dramatic effect on increasing CO production but not on H2 . Formate was also increased under UV light. Overall, the present study provides strategies of controlling reduction products and syngas ratio by employing hybridized ZGO/ZnONR, doping, and UV light. Graphical Abstract: ga1 Highlights: Eu(III)-doped ZnGa2 O4 nanoparticles, and ZnGa2 O4 hybridized ZnO nanorods were prepared. Photocatalytic and photoelectrocatalytic CO2 reduction were tested with variable parameters. CO, CH3 OH, and CH4 were detected in photocatalytic CO2 reduction. H2, CO, and formate were observed in photoelectrocatalytic CO2 reduction. Syngas (H2 /CO) ratio was controlled from 0.5 to 2.0 by hybridizing ZnGa2 O4 on ZnO.